Female Identity and Agency in the Cult of the Martyrs in Late Antique North Africa - Barkman, Heather (Université d'Ottawa / University of Ottawa, 2016)
This thesis investigates the dual roles that women played in the cult of the martyrs in Christianity in Late Antiquity: as martyrs worthy of admiration and as venerators engaged in acts of celebration. The investigation is driven by questions regarding the identity, agency, and power of women in the cult of martyrs, focusing on late antique (second- to fifth-century) North Africa. Late antique Christians expressed their veneration of the martyrs in a variety of ways, including (but not limited to) special church services, praying for the martyrs, visiting martyrs’ shrines to ask for miracles (often healing in nature), and partaking in commemorative feasts at the martyrs’ graves on the anniversaries of their deaths. In all of these modes of veneration, women took on various roles that were analogous with other roles outside of the cult of the martyrs, such as wife, mother, patron, or client. Female martyrs are also identified using these roles, and thus this provides a useful area of comparison. By exploring these roles, this thesis arrives at a more nuanced understanding of women’s agency and power in traditional contexts and how such agency and power were transferred, continued, and challenged within the cult of the martyrs. The thesis engages in textual and discourse analysis of the relevant primary sources, particularly the martyr texts, sermons, letters, and treatises by North African writers. In the secondary literature, this study engages with the diverse works of classicists, historians, archaeologists, religious studies scholars, and feminist theorists. The interdisciplinary approach of the thesis is further nuanced by an examination of the concepts of identity, agency, and power. Applying these analyses to the context of women’s participation in the cult of the martyrs provides new insights into how we can uncover women’s experiences in ancient sources, where women’s voices are almost always obscured by male discourses.
Keywords: Women; Martyrs; Late Antiquity; North Africa